2022
DOI: 10.1101/2022.10.07.511294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hexanematic crossover in epithelial monolayers depends on cell adhesion and cell density

Abstract: During tissue folding in developmental processes and monolayer migration in wound healing, epithelial cells undergo shape changes and move collectively. Recent experimental and numerical results suggested that these processes could leverage on the existence of both nematic (2--fold) and hexatic (6--fold) orientational order coexisting at different length scales within the same epithelial layer. Yet, how this remarkable example of multiscale organization in living matter is affected by the material properties o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, previous experiments conducted on unpatterned substrates have concluded that HBEC monolayers could be described as a turbulent active nematic phase with half-integer topological defects 5 . To reconcile these seemingly contradictory findings, we analyzed how the local order scaled with the size 𝑅 of the window over which this order parameter was computed 44 (see Supplementary Notes 5.7). For randomly oriented 𝑁 particles, the order parameter scales as 1 √𝑁 as a consequence of the central limit theorem, and therefore as 1 𝑅 in two dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous experiments conducted on unpatterned substrates have concluded that HBEC monolayers could be described as a turbulent active nematic phase with half-integer topological defects 5 . To reconcile these seemingly contradictory findings, we analyzed how the local order scaled with the size 𝑅 of the window over which this order parameter was computed 44 (see Supplementary Notes 5.7). For randomly oriented 𝑁 particles, the order parameter scales as 1 √𝑁 as a consequence of the central limit theorem, and therefore as 1 𝑅 in two dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…in active migration force [56] or in proliferation-dependent cell size [57]). Other interesting directions would be to incorporate the effect of active nematics and turbulence [58][59][60][61][62] or to consider alternative theoretical modes of mechano-sensitive couplings which have been recently proposed, for instance on junctional tensions driving active cell rearrangements [34] or junction remodelling [34,63,64]. Finally, while we have considered a minimal model of ERK dynamics and its coupling to mechanics, considering more complex features of the pathway such as activator-inhibitor dynamics [65] would be an important next step.…”
Section: Discussionmentioning
confidence: 99%